PRINSIP HUKUM DALAM KONTRAK KERJASAMA KEGIATAN USAHA HULU MINYAK DAN GAS BUMI - Sang Ayu Putu Rahayu (Universitas Airlangga, 2017)
The main issues elaborated in this legal research are the legal principles of tender during a pre-contractual stage and the principles of contract law on Cooperation Contract known as Production Sharing Contract (PSC) based on Laws Number 22 Of 2001 Concerning Oil and Gas. The type of this research is normative study and the approach of this research are conceptual approach, statute approach, and case approach. There are two results in this research. Firstly, in the process of tender during a pre-contractual stage of Cooperation Contract, the principles of responsive competition, transparency and the principle of accountability must be applied. The principle of responsive competition is the most important to be implemented since the tender process produces a competition to get a working area. In addition, the tender process of Cooperation Contract is also related to the principles of transparency and accountability that plays to protectthe interests ofthe state and to get a competent contractor.Secondly, in formation and performance of the Cooperation Contract, the principle of proportionality sharing should be emphasized, especially when formulating the proportion of production sharing. Cooperation Contract is also related to the principle of transparency that plays an important role on state revenues from the upstream oil and gas business activities, because a transparent process will result in optimal outcomes. Finally, in Cooperation Contract, the principles of responsive competition, transparency, accountability, and the principle of proportionality sharing should be clearly stated in the rules and legal norms.